THE INVISIBILITY IN THE PRESS OF DEGRADED RIVERS AS FACTORS CAUSING THE WATER CRISIS IN SÃO PAULO (2012-2016) (Comunicação & Inovação, 2024)
This article presents some of the key findings of the PhD thesis (Oliveira, 2019) on the water crisis in São Paulo (2012-2016). One of the main objectives was to understand whether the press addressed the pollution of urban rivers and reservoirs as one of the causes of the shortage of potable water during this period. The main hypothesis was that the digital journalistic coverage had not gone back far enough in time to identify one of the factors relevant to the water shortage: the historical degradation of urban rivers. The study combines Time Cut Analysis and Framing Analysis.
Keywords: Português